Characterization of the Physical Stability of a Lyophilized IgG1 mAb after Accelerated Shipping‐Like Stress. Issue 2 (17th December 2014) - Telikepalli, Srivalli; Kumru, Ozan S.; Kim, Jae Hyun; Joshi, Sangeeta B.; O'Berry, Kristin B.; Blake‐Haskins, Angela W.; Perkins, Melissa D.; Middaugh, C. Russell; Volkin, David B.
<x xml:space="preserve">Abstract</x> Upon exposure to shaking stress, an IgG1 mAb formulation in both the liquid and lyophilized state formed subvisible particles. Because freeze‐drying was expected to minimize protein physical instability under these conditions, the extent and nature of aggregate formation in the lyophilized preparation were examined using a variety of particle characterization techniques. The effects of formulation variables such as residual moisture content, reconstitution rate, and reconstitution medium were also examined. Upon reconstitution of shake‐stressed lyophilized mAb, differences in protein particle size and number were observed by microflow digital imaging, with the reconstitution medium having the largest impact. Shake stress had minor effects on the structure of protein within the particles as shown by SDS‐PAGE and FTIR analysis. The lyophilized mAb was shake stressed to different extents and stored for 3 months at different temperatures. Both extent of cake collapse and storage temperature affected the physical stability of the shake‐stressed lyophilized mAb upon subsequent storage. These findings demonstrate that physical degradation upon shaking of a lyophilized IgG1 mAb formulation includes not only cake breakage, but also results in an increase in subvisible particles and turbidity upon reconstitution. The shake‐induced cake breakage of the lyophilized IgG1 mAb formulation also resulted in decreased physical stability upon storage. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:495–507, 2015